INOVASI PELAYANAN RAPOR BERBASIS ONLINE DI SMA IPIEMS SURABAYA - Irfan Dwi Saputra; Hidayat Eko Novanto; Muhammad Arifin; Diana Hertati (Journal Publicuho, 2020)
Online report card is a web-based value management system created by utilizing technology in its process to overcome the fundamental problems of processing and reporting grades in the 2013 Curriculum. Online report cards have been applied in various schools in the Surabaya area and currently the application has spread to various regions of Indonesia. In the application of online report cards there are various positive and negative impacts felt by the community. The research aims to analyze and see how the innovation of online report card services at IPIEMS Surabaya High School. The method used in this research is descriptive qualitative approach with data collection techniques using riview literature. The focus in this research is based on Everett M Rogers' theory of innovation attributes, namely relative advantage, suitability, complexity, probability, observability. The results of the analysis in the study using the attribute theory of online report card service innovation at IPIEMS Surabaya High School are in accordance and meet the 5 elements of innovation attributes by Everett M Rogers. Online report card service innovation implemented at SMA IPIEMS Surabaya can be carried out effectively and efficiently, besides that there is still a lack of relative benefits that do not cover the whole of online report card innovation